The first rodent behavioral study (1822) and the diffusion of human-bred albino rats and mice in the 19th century - d’Isa, Raffaele (Frontiers in Psychology, 2025)
Rodents, in particular rats and mice, are currently the most widely employed animal models in psychology and behavioral neuroscience. Nevertheless, an interesting historical question is: when was the first rodent behavioral study performed and by whom? The current article presents the first rodent behavioral study in the history of science: a case of interspecies social bonding between a rat and a dog, observed in 1822 by the British chemist Samuel Moss (1794–1868) and subsequently described by the same in a scientific article in 1836. In the present article, after a biographical sketch of Samuel Moss, I examine in detail the notable case of interspecies bonding observed by Moss. This case is notable under several points of view. First, Moss’s rat was an albino, a variety which at that time was extremely rare. Moreover, at that time, in the Western world rats were mostly seen as pest animals or baits for rat-catching sports, and were not kept as pets. The color of the rat played a key role in its fate, being the reason for which it was originally brought to Moss and for which Moss decided to keep it under his care. Third, the relationship that arose between the rat and the dog is even more surprising if we consider that the dog was a trained rat-catcher. Importantly, this rat-dog bonding case, which showcased the tameness of Moss’s albino rat in both lay and scientific publications, represented the first popularization of the docility of albino rats. After having outlined Moss’s case, considering the importance of albino rats in our current society, both in scientific research (where the albino rat has become the prototype of the laboratory rat) and as pets, I provide an historical contextualization regarding albino rodents, starting from the 17th century, and I then trace the history of the post-Moss diffusion of human-bred albino rats and mice in the 19th century.